Psychosocial and sociocultural characteristics of Nicaraguan and Costa Rican students in the context of intercultural education in Costa Rica - Campos Saborío, Natalia (2018)
This article examines problems and difficulties encountered by Nicaraguan migrant students in the Costa Rican educational system and contrasts their psychosocial and sociocultural well-being with their Costa Rican counterparts. The findings point out not only the differences in educational outcomes between these cohorts, but also highlight the prevalence of psychosocial risk behaviors related to violence, bullying, death wishes and self-injury experienced by Nicaraguan students. Furthernore, there appears to be a large gap between the stated objectives and policies of the Costa Rican educational system to recognize and foster intercultural understanding and tolerance and the educational results of its minority population, especially Nicaraguan students. The conclusions drawn from these case studies identify the importance of closing the gap between the well- intended national educational policies and the actual educational practice in order to promote equitable and social justice learning in Costa Rica and better the chances for integration of its Nicaraguan minority.